34. Effectiveness of school and communication-based interventions for the prevention of burns among secondary school students in Vu Thu district, Thai Binh province - Linh, Vu Gia; Hai, Vu Minh; Vung, Nguyen Dang (Tạp chí Nghiên cứu Y học, 2024)
The study aimed to evaluate the effectiveness of school- and community-based interventions in improving knowledge and practice of burns prevention for secondary school students in Vu Thu district, Thai province. We conducted a controlled community trial in the Vu Thu district, Thai Binh province. The self-administered structured questionnaire, which was developed under the instruction of experts in burn injury prevention, and the information page of the Ministry of Health and the Ministry of Education and Training, was used in this study. The effectiveness of the intervention was evaluated by comparing the effectiveness index before and after the intervention between the intervention group and the control group. Among 2028 secondary school students, the score of knowledge about burn prevention in the control group and the intervention group increased after intervention (from 6.238±2.050 to 6.847±2.033 and from 6.257±2.112 to 7.314±1.824, respectively). Knowledge scores on recognizing the causes and ways to prevent burns tend to increase after the intervention, especially in students with higher knowledge scores on these two topic groups than the control group. It is similar to the score of practice in preventing burn injuries, from 6.047±3.582 to 6.247±3.660 in the control group and from 6.638±3.411 to 7.342±3.207 in the control group. The effectiveness of the intervention has contributed to increasing secondary school students’ knowledge and practice of preventing injuries caused by burns. Therefore, it is necessary to continue research in secondary schools, especially in suburban areas and other provinces, to obtain reliable evidence for policy development and planning for injury prevention - burning injuries.